Methodological aspects of prediction of distribution of alien species on the basis of phytoindication (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The penetration of the invasive species into the natural habitats will be successful if ecological optimum of most factors for invading species coincides with the stress zone of these factors for the habitat, that means entering the value range of, so called, «reduced coenotic competition». The hypothesis was verified following analysis of 2,736 geobotanical descriptions of plant communities from the territory of Prut and Siret high basins. This flora includes 106 adventive species and 5 species-transformers among them. There was analyzed the coinciding degree of the ranges of model species’ tolerance zones (Erigeron annuus (L.) Desf. (species-transformer), Cichorium intybus L. (invasive species), Sisyrinchium septentrionale E. P. Bicknell (invasive species) and communities towards 12 leading ecological factors such as soil hydrological regimen (Hd), humidification variability (fH), aeration (Ae), acidity (Rc), salification (Tr (Sl)), soil carbonate content (Ca), content of assimilable nitrogen (Nt), thermal regimen (Tm), climate humidity (Om), climate continentality (Kn), climate hardness (Cr), light regimen (Lc)). It was found that the model species are present only in the plant communities, where total overlap of tolerance zones of leading ecological factors reach 80–100%. The authors have formed 3D-models that illustrate correlation between the overlap level of species ecological optimum, stress zone and plant communities ecological optimum, which can be used for estimation of alien species invasive possibilities and detecting potential plant communities for their adoption.
Keywords: plant communities, alien species, ecological factors, ecological optimum, stress zone, models.